Karakterisasi Molekuler Bakteri Probiotik Ikan Kerapu Bebek Berbasis Teknik 16S Ribosomal DNA - Feliatra, Feliatra; Andrito, Wahyudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2007)
The aim of research was to find the molecular characteristics of probiotic bacteria in the digestive tract of grouper fish (Chromileptes altivelis) based on 16S ribosomal DNA technique. The bacteria were isolated from stomach and intestine of the fish and were analized in the Marine Microbiology Laboratory of fishery and marine Science Faculty of Riau University. The bacterial DNA were isolated by using a PCR (polymerase Chain Reaction) and was conducted in the biotechnology laboratory of Diponegoro University, Semarang. The purified DNA was sequenced in the BPPTTangerang. Result shown that 6 bacterial species may be potential as probiotic. There were Bacillus velesensis strain CR-11, Vibio alginolyticus A3G-2, Bacillus cereus site2S, uncultured bacterium clone BB3S16S-17, Bacillus subtillus strain CICC10066, and Bacillus flexus strain LF-3. these bacteria grow well at pH 2 and this indicated one of probiotic bacteria characteristics.